MOTIVASI KERJA SEBAGAI DETERMINAN KINERJA KARYAWAN PADA SEKTOR PERBANKAN SYARIAH - Aqsa, Muhammad Ali (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the effect of work motivation on employee performance in the Islamic banking sector in Indonesia, with a case study at a Sharia People's Financing Bank (BPRS) in Pekanbaru. The research sample consisted of 37 people, taken using the census method. Data analysis used simple linear regression. The results of the partial t-test show that work motivation has a significant effect on employee performance at the BPRS (t-count = 4.477 > t-table = 2.035). The magnitude of the effect of work motivation on employee performance is 36.4% (R² = 0.364). Based on these findings, it is recommended that management strengthen the relationship between superiors and subordinates to create a harmonious work climate, considering that this aspect received the lowest response from respondents. The results of this study are expected to provide input for the development of more effective human resource management systems in Islamic financial institutions.